Qualitative and financial evaluation of public and private forest nurseries; Case study of southern Zagros forests, Iran - MARYAM FAZLOLLAHI MOHMMADI; SEYED MAHDI HESHMATOL VAEZIN; VAHID ETEMAD; ASHGAR SEPAHVAND; ANOSHIRVAN SHIRVANI; SOLEIMANI AZAM (Nusantara Bioscience, 2014)
Abstract. Mohammadi MF, Vaezin SMH, Etemad V, Sepahvand A, Shirvani A, Azam S. 2014. Qualitative and financial evaluation of public and private forest nurseries; Case study of southern Zagros forests, Iran. Nusantara Bioscience 6: 152-158. This study has examined the efficiency of two nurseries, private and public divisions, based on qualitative and financial evaluation in the Southern Zagros forests of Iran. To achieve this purpose, we selected two species including pistachio (Pistacia atlantica) and poplar (Populus nigra) in one year period. Results of qualitative evaluation showed that all produced seedlings by private nursery significantly had better features than the public one at a significant level of 0.05. Also, the results of financial evaluation showed that cost price of each poplar seedling at private nursery (0.734 $) was 19.6 times less than public one (14.4 $). The interest rate for pistachio seedling in private sector ranges from 1.9 to 2.2 $, while it ranges from 1.5 to 1.9 $ for poplar seedling. Such researches may help to improve management as well as financial and qualitative efficiency, especially in public nurseries. Future researches will be required to document other aspects of private management on nurseries in seedling products.